Purification and Partial Characterization of Draculin, the Anticoagulant Factor Present in the Saliva of Vampire Bats (Desmodus rotundus) - Apitz-Castro, Rafael; Béguin, Suzette; Tablante, Alfonzo; Bartoli, Fulvia; Holt, John C; Hemker, H Coenraad (Thrombosis and Haemostasis, 1995)
From the saliva of the vampire bat Desmodus rotundus, we isolated an unknown anticoagulant protein which we have named draculin. Its molecular mass as determined by non-reduced SDS-PAGE is about 83 kDa. The reduced polypeptide shows a slower migration. HPLC in a molecular sieve matrix yields a single, symmetrical peak corresponding to 88.5 kDa. Isoelectric focusing shows an acidic protein with pI = 4.1–4.2. Aminoacid analysis is compatible with a single chain polypeptide of about 80 kDa. Cyanogen bromide cleavage yields a single 16-aminoacid peptide, corresponding to the amino-terminus of the native molecule. Draculin inhibits the activated form of coagulation factors IX and X. It does not act on thrombin, trypsin, chymotrypsin and does not express fibrinolytic activity. The inhibition is immediate and not readily reversible, with a stoichiometry of about two molecules of draculin per molecule of factor IXa or Xa. Surprisingly, the inhibitory activity against either factor is not affected by the presence of the other. Draculin binds quantitatively to either immobilised factor Xa or factor IXa. Our preliminary interpretation is that there are two forms of draculin that hardly differ in structure. Both bind to factor Xa and to factor IXa but one form inhibits factor Xa and the other inhibits factor IXa.When added to plasma, draculin increases the lag phase as well as the height of the peak of thrombin generation.